Genome-guided comparative in planta transcriptome analyses for identifying cross-species common virulence factors in bacterial phytopathogens - Park, Jungwook; Jung, Hyejung; Mannaa, Mohamed; Lee, Seung Yeup; Lee, Hyun-Hee; Kim, Namgyu; Han, Gil; Park, Dong-Soo; Lee, Sang-Won; Lee, Seon-Woo; Seo, Young-Su (Frontiers in Plant Science, 2022)
Plant bacterial disease is a complex outcome achieved through a combination of virulence factors that are activated during infection. However, the common virulence factors across diverse plant pathogens are largely uncharacterized. Here, we established a pan-genome shared across the following plant pathogens: Burkholderia glumae, Ralstonia solanacearum, and Xanthomonas oryzae pv. oryzae. By overlaying in planta transcriptomes onto the pan-genome, we investigated the expression profiles of common genes during infection. We found over 70% of identical patterns for genes commonly expressed by the pathogens in different plant hosts or infection sites. Co-expression patterns revealed the activation of a signal transduction cascade to recognize and respond to external changes within hosts. Using mutagenesis, we uncovered a relationship between bacterial virulence and functions highly conserved and shared in the studied genomes of the bacterial phytopathogens, including flagellar biosynthesis protein, C4-dicarboxylate ABC transporter, 2-methylisocitrate lyase, and protocatechuate 3,4-dioxygenase (PCD). In particular, the disruption of PCD gene led to attenuated virulence in all pathogens and significantly affected phytotoxin production in B. glumae. This PCD gene was ubiquitously distributed in most plant pathogens with high homology. In conclusion, our results provide cross-species in planta models for identifying common virulence factors, which can be useful for the protection of crops against diverse pathogens.